Basque Traces in the Toponymy of Newfoundland and Various Coasts of Atlantic Canada - Weyers, Christian (York University, 2009)
Whereas the first and undoubtedly most important toponymic stratum of the island of Newfoundland and adjacent waters is Portuguese, the presence of Basques from the 1530s to the late 17th century on the South and West coasts of Newfoundland, the islands of Cape Breton, Saint-Pierre and Miquelon and on the left bank of the Saint Lawrence River had relatively little impact on the geographical nomenclature. Documentation is rare and not readily accessible, and the omnipresence of French during this period was not at all favorable to the development of appellations given by French and Spanish Basques. Many names are now extinct, others have been Frenchified and Anglicized ('Port au Port', 'Port au Choix', 'Ingornachoix'). The most complete repertory of Basque names (although many of them are mixed or hybrid appellations) is to be found in Pierre Detcheverry’s edition of the rutter of Martín de Hoyarçabal (Bayonne 1677). In contrast, his map of 1689 and that of Denis de Rotis (1676) offer only a relatively small number. An accurate comparison of maps and charts from the 16th and 17th century until today will show to what extent Basque names – including those of minor geographical features – have stayed, been altered or vanished completely. Other categories, e.g., the commemorative names ('Lac de ~' and 'Anse de l’Échafaud du Basque', 'Basque Island', etc.) and name transfers of places of origin with reference to the Basque Country ('Amuitx', 'Plasencia') – some of them hypothetical ('Cape Breton') – will also be discussed in this paper.